2014
DOI: 10.1111/apa.12551
|View full text |Cite
|
Sign up to set email alerts
|

Infant growth is associated with parental education but not with parental adiposity – Early Stockholm Obesity Prevention Project

Abstract: Low parental education level is independently associated with infant growth, whereas parental obesity does not contribute to a higher weight or to rapid weight gain during the first year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 29 publications
3
20
1
Order By: Relevance
“…That fact that heredity is of importance for overweight is well documented in the literature . So is parental educational level , which was in accordance with our results. Parental smoking can be considered as a proxy, namely surrogate variable, for socioeconomic background.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…That fact that heredity is of importance for overweight is well documented in the literature . So is parental educational level , which was in accordance with our results. Parental smoking can be considered as a proxy, namely surrogate variable, for socioeconomic background.…”
Section: Discussionsupporting
confidence: 94%
“…Risk factors for overweight and obesity include high birthweight , heredity , high maternal weight gain during pregnancy , formula feeding , rapid growth during infancy and a low parental educational level . There are also data showing a correlation between obesity and disturbances in the gut microbiota .…”
Section: Introductionmentioning
confidence: 99%
“…The associations found between income and child BMI SDS, and not with parental education, are surprising since most previous studies but not all have found low parental education to be a risk factor for childhood obesity. However, there are few studies measuring the influence of both education and income on childhood obesity like ours; more research is needed to examine the impact of each SES indicator taking also into account the strengths of social relationships, thus the social capital.…”
Section: Discussioncontrasting
confidence: 57%
“…Low parental socioeconomic status (SES) is associated with an increased risk for childhood obesity (1)(2)(3)(4)(5). Some studies suggest that parent social support is also associated with child obesity risk (6).…”
mentioning
confidence: 99%
“…A greater number of studies assessed infant growth (weight and/or height) trajectories and SEP; however, it is worth noting that several examined overall infant growth in the population [104][105][106][107], rather than rapid infant growth [108][109][110]. Studies from the Netherlands, Australia and the UK found no association between infant growth and SEP [104,105,108] (with the Australian study assessing rapid infant weight gain), with four European studies from the UK, Netherlands and Sweden finding an inverse association [106,107,109,110] (Wiljaars finding an association with rapid weight gain and Svensson finding an association with overall weight gain but not rapid weight gain). Only two studies were conducted in low-or middle-income countries, with a positive association observed in infants from both Belarus [111] and Chile (noting that the Chilean sample excluded babies <3 kg at birth) [112].…”
Section: Rapid Infant Growth and Early Adiposity Reboundmentioning
confidence: 99%